School-based mental health screenings with Ukrainian adolescent refugees in Germany: Results from a pilot study - Catani, Claudia; Wittmann, Jasmin; Schmidt, Telja Lucia; Wilker, Sarah; Neldner, Sina; Neuner, Frank (Frontiers in Psychology, 2023)
Since the Russian invasion of Ukraine in February 2022, high numbers of Ukrainians, mostly women and children, have left the country. As of today, Germany has accepted more than one million refugees fleeing from Ukraine including 200,000 children and adolescents registered in German schools. Since refugee minors are typically affected by high rates of mental health issues, the identification of potential psychological problems at an early stage after arrival is essential in order to make timely referrals for vulnerable youth to diagnostic or treatment services possible. The aim of the present study was to test the feasibility of a classroom-based mental health screening procedure and to assess symptoms of PTSD, depression, and anxiety in a small sample of adolescents who had fled to Germany. Forty-two adolescents (n = 20 girls) took part in the study. Screening results showed that more than half of the sample had elevated ratings in the Refugee Health Screener (RHS) and about 45% reported clinically significant levels of PTSD. Overall, the amount of both mental health problems and current worries related to the war was significantly higher in girls compared to boys. In general, screenings were well received by the adolescents. The findings of this pilot study point to a considerable level of mental health problems and distress in adolescent refugees affected by the recent war in Ukraine. Brief psychological screenings within the school setting might represent a promising approach to identifying potential mental health disorders as early as possible in newly arriving refugee youth.